Characterization and typification of small-scale goat production systems in the highlands of southeast Peru - Walter Palomino Guerrera; David Godoy Padilla; Joseen Huaripaucar Huancahuari; Joseen Huaripaucar Huancahuari; Emmanuel Sessarego Dávila; Fritz Trillo Zárate; Juancarlos Cruz Luis (Pastoralism)
Goat breeding in Peru is one of the main activities of smallholders. Goats are distributed in different agroecological zones and regions of the country, developing under heterogeneity of production systems, making it difficult to understand goat breeders’ socioeconomic, technological, and productive situations. This study aimed to characterize and typify the goat production systems in the highlands of southeast Peru. A survey was conducted with 91 goat farmers from five districts of Ayacucho, Peru, using a structured and individualized questionnaire administered on their farms. The socio-economic, productive, and commercial characteristics of the goat production systems were recorded. A multiple correspondence analysis (MCA) and hierarchical classification analysis (HCA) were performed to establish a typology of the smallholders. The results reveal that the breeding system is extensive, where there is no breeding program, with natural pastures and crop stubble being the source of food for the herds. Only slightly more than half (54%) carry out a deworming program. Farmers were categorized into three different groups, corresponding to three different farming systems: Group 1 farmers raised goats solely for home consumption; Group 2 breeders raised goats for both consumption and marketing of surplus products (cheese, milk, and meat), and Group 3 farmed focused on producing cheese and goat kids and selling to local markets. The study provides valuable insights that will help design effective breeding strategies to develop sustainable goat farming in the region, considering different production systems and their respective socio-economic and trade dynamics. This classification will be essential for tailoring development programs to the specific needs of each group, promoting better use of resources, improving productivity, and enhancing the livelihoods of smallholder goat producers in Peru.